Reparameterizing Tectonics Perception on Planar Material-Design - Stephanus Evert Indrawan; Gervasius Herry Purwoko; Tri Noviyanto P. Utomo (Graduate School of Institut Seni Indonesia Yogyakarta, 2019)
Indonesia is known as a country rich in types of building materials and technologies inherited from generation to generation. Along with the passage oftime appears the computer as a human tools. However during the materialsprocessing this computational approach is still separated. Computers are still usedas tools for drawing and not used as design tools in the design thinking process.Computational design has an ability to integrating the design focus from thematerial side, structure, and formation associated with digital fabrication. Thispaper focuses to divide concepts of tectonics as general and relate them to theunderstanding of digital perception. This paper also presents the results of a studythat has involved digital perception in the study of planar materials and wafflestructure systems from the early stages to the model of construction. Plywood isthe only material used, made with milling machines and built by students. Thisprocess introduces students to different experience of the design process.Computational design makes possibilities to integrating the design focus from thematerial side, structure, and formation associated with digital fabrication.